Teachers' Perspectives on The Abolition of The National Exam: Navigating the Debate in Indonesia - Sari Trisnaningsih; Jovita Ridhani (Indonesian Journal of Instructional Media and Model, 2024)
This study explores how teachers perceive the abolition of the national exam and how the reform impacts their classroom practices in accordance with Michael Fullan's work on educational change and reform. This qualitative case study reports on data gathered via a semi-structured interview with Indonesian biology teachers, who have experience of the national exam. The findings show that teachers have complex and nuanced opinions about the abolition of the national exam. The results reveal that teachers hold nuanced perspectives on the abolition of the national exam, shaped by negative views of the exam, prior policy changes, and concerns about teaching practices. The results also highlight: (1) Teachers have embraced updated curriculum practices, broadening the scope of content, ensuring equal attention to all subjects, and moving away from intense exam-focused preparation; (2) They have adopted more flexible and diverse teaching strategies, allowing for greater use of experimental activities and fostering collaborative learning with students; and (3) The shift has encouraged teachers to reflect on and reconsider their pedagogical beliefs, prompting a deeper examination of the assumptions and frameworks that guide their teaching practices. These findings suggest that abolishing the national exam has not immediately led to radical changes but has had positive implications for classroom instruction.